The relationship between pain and clinical parameters, depression, anxiety and sleep quality in patients with spinal injury - Balikci, Sibel; Bardak, Ayse Nur (Journal of the Pakistan Medical Association, 2022)
Objective: To examine the frequency of pain in individuals with spinal cord injury, and to assess the relationship of pain with functional status, sleep quality, anxiety and depression levels. Method: The prospective, cross-sectional study was conducted from March to June 2018 at Istanbul Physical Medicine and Rehabilitation Training and Research Hospital, Istanbul, Turkey, and comprised adult patients of wither gender with spinal cord injury who were in the rehabilitation phase both on outpatient and inpatient basis. Data was collected using a questionnaire exploring demographic and clinical features. The presence of pain was assessed using the Leeds Assessment of Neuropathic Symptoms and Signs scale and, in case pain was found present, it was categorised as neuropathic, nociceptive and mixed type pain types. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index, while the Hospital Anxiety and Depression scale was used to evaluate anxiety and depression levels. Data was analysed using SPSS 20. Results: Of the 150 patients, 104(69.3%) were males and 46(30.7%) were females. The median age of the sample was 46 (IQR:20.52) years. Neuropathic pain was observed in 61(40.7%) patients, nociceptive in 32(21.3%) and mixed type in 12(8%). Depression was found in 71(47.3%) patients, poor sleep quality in 41(27.3%) and anxiety in 35(23.3%). Sleep, anxiety and depression scores were higher in the presence of neuropathic and nociceptive pain (p<0.05). Conclusion: Pain is a common complication in patients with spinal cord injury. In the presence of pain, sleep quality is worse, and anxiety and depression levels are high. Key Words: Spinal cord injury, Pain, Sleep quality, Anxiety, Depression.